Phase separation behavior of poly(methyl methacrylate)/poly(styrene-co-maleic anhydride) in the presence of hollow silica nanotubes. Issue 71 (5th December 2018) - Lv, Xiong; Zuo, Min; Zhang, Haimo; Zhao, An; Zhu, Weipu; Zheng, Qiang
Abstract : The applicability of Arrhenius equation to the phase separation behaviors for filled systems indicates that HSNTs results in the decline of temperature sensitivity for phase separation rate, but hardly changes the viscous diffusion essence of chains. Abstract : The phase separation behavior of poly(methyl methacrylate) (PMMA)/poly(styrene- co -maleic anhydride) (SMA) blends with and without one-dimensional hollow silica nanotubes (HSNTs) was investigated using time-resolved small-angle laser light scattering. During isothermal annealing over a range of 100 °C above the glass transition temperature, the Arrhenius equation is applicable to describe the temperature dependence of phase separation behavior at the early and late stages of spinodal decomposition (SD) for unfilled and filled PMMA/SMA systems. The mechanical barrier effect of HSNTs on the macromolecular chain diffusion of the blend matrix may retard the concentration fluctuation at the early stage and slow down the domain coarsening at the late stage of SD phase separation for the blend matrix to result in the decrease of apparent diffusion coefficient D app, the postponement of the relaxation time and the decline of temperature sensitivity for the phase separation rate.